New Zealand's response to the crises in Africa : a thesis submitted for the degree of Doctor of Philosophy, Massey University, Albany, Auckland, New Zealand - Chile, Love Mngohol (Massey University, 1996)
The thesis seeks to explain the motivation for New Zealand's response to the sociopolitical and economic crises in Africa. New Zealand's response is conceptualised to include 'foreign aid' as well as the non-traditional forms of international assistance such as peacekeeping and monitoring, political and moral support on issues such as apartheid. Qualitative research methodology is used to critically examine both the official bilateral response and the response of the non governmental organisations (NGOs). In the context of existing theory, New Zealand's response to the crises in Africa has significant elements of both the functional utility approach (McKinley and Little 1977) and the conventionalist framework (Gordenker 1976). Official policy espouses both, although the balance between the pursuit of foreign policy interests and altruistic response to the crises is difficult to attain. The thesis concludes that while New Zealand's political and moral response was an important factor in the resolution of the crisis of apartheid, the overall official response to the socioeconomic and developmental crises is ineffective. Development partnership between New Zealand NGOs and local NGOs and communities in Africa has been a more effective response to the developmental crises. International development partnership with African countries and communities based on longer term commitment to processes which enhance sustainable socioeconomic progress and social justice is recommended as a strategy for maximising the effectiveness of international response to the crises in Africa.
Keywords: Foreign relations; Foreign economic relations; Economic assistance; Economic aid; New Zealand; Africa